MODERNIZATION OF MILLING MACHINES MA665 WITH NUMERICAL CONTROL - Matkarimov Behzod Baxtiyorjon o'g'li; Omonov Abdukaxxor Abdiraxmon o‘g‘li (International Journal of Innovations in Engineering Research and Technology, 2021)
The goal is to consider the use of modernization of outdated metal-cutting equipment for modern technological tasks as one of the economically feasible options, alternative to the purchase of new expensive equipment. The use of aggregation allows in the process of modernization to create technological equipment for a specific group of products with the implementation of an optimal technological process. Simultaneous equipping of the machine with a modern control system, as well as assemblies and equipment for CAMtechnologies and HSM-technologies, allows you to get a qualitatively new equipment. The article shows the practical experience of modernizing the MA665 milling machine for tool processing. It describes a deep modernization with a complete replacement of all drives, electrical and control systems.